Produtividade de algodão herbáceo (Gossypium hirsutum L.) em função das adubações de plantio e foliar com fertilizante organomineral - Lançoni, Rafaela (Universidade Federal de São Carlos, 2018)
The current cotton culture model in Brazil is characterized by extensive agricultural areas, especially in the Midwest region. The mega-cotton system has been criticized due to the difficulties of conducting it sustainably. Modern varieties have been genetically improved to achieve high productivity and require greater amounts of fertilizers. In input-intensive crops, managed under a conventional system, the inappropriate use of mineral fertilizers increases the environmental risks and economic losses with fertilization, which represents 15% of the production costs of the cotton crop. The objectives of this study were: (i) to cultivate herbaceous cotton, variety IAC 27 RDN (80,000 plants ha-1), submitted to planting fertilization with mineral fertilizer (MF) and with organomineral fertilizer (OMF) (Cooperhúmus®); (ii) verify the effects of foliar application of fertilizer based on amino acids (Aminomagma®); (iii) evaluate biometric, nutritional, and production parameters. The experiment was conducted from 12/2017 to 06/2018, in a dystrophic Oxisol, with an experimental design in five randomized blocks and the following treatments: T0 - without fertilization; T1 - MF at planting (580 kg ha-1 NPK 04-14-08); T2 - MF at planting + leaf amino acids; T3 - OMF at planting (625 kg ha-1 NPK 04-14-06); T4 - OMF at planting + leaf amino acids. The quantity of fertilizers was calculated for the expectation of productivity of 2.5 t ha-1 of cottonseed and the covering fertilization was carried out with 175 kg ha-1 of MF NPK 30-00-10. Aminomagma® was sprayed at 57 days after emergency (DAE) and 82 DAE. The following were evaluated: plant height (PH, m) at 29, 55 and 89 DAE; weight of apples (WA, g plant-1), at 89 DAE; productivity (kg ha-1), at 180 DAE. The sampling of diagnostic leaves occurred at 96 DAE for analysis of leaf contents of N, P, K, Ca, Mg and S. The results were subjected to analysis of variance and, when significant by the F test (p <0.05), were deployed for comparison by the Scott-Knott test (p < 0.05). The leaf contents of N, P, Ca, Mg and S were adequate, but there was K insufficiency. The treatments did not interfere in the WA, in the productivity and in the leaf contents of N, P, K, Ca, Mg and S. The use of Cooperhúmus® at planting (T3) resulted in plants with greater height at the beginning (29 DAE) and at the end (89 DAE) of the vegetative stage of the culture. Aminomagma® promoted an increase in the final height of the plants only when mineral fertilizer was used in planting (T2), with a similar result to the isolated use of Cooperhúmus® in planting (T3). Planting fertilization with Cooperhúmus® is recommended because, in addition to resulting in taller plants at 29 DAE, which is important for establishing the plant in the field, and productivity similar to that achieved with conventional fertilization, organomineral fertilizer improves chemical, physical, and biological soil attributes and minimizes negative environmental impacts resulting from nutrient loss routes, due to its slow and gradual availability of the elements.
Yield of herbaceous cotton (Gossypium hirsutum L.) as a function of planting and leaf fertilizations with organomineral fertilizer
Keywords: IAC 27 RDN; Tecnologia de fertilizantes; Adubação foliar; Aminoácido; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FERTILIDADE DO SOLO E ADUBACAO